Overcoming Barriers to Service Access: Refugees' Professional Support Service Utilization and the Impact of Human and Social Capital - Ellen Heidinger (Journal of International Migration and Integration, 2022)
After arriving in a new country, refugees are typically dependent on professional support to re-establish their livelihood. However, it is well documented that refugees face barriers when seeking access to services aimed at facilitating their settlement. This study examines refugees' support service needs, their actual utilization, and investigates the impact of social and human capital on service utilization. Using data from the IAB-BAMF-SOEP Survey of Refugees (2016–2019; N =7662), this paper, employing nested logistic regression models, highlights the diversity of refugees' support service needs as well as large differences in utilization across eight different domains during the first couple of years after arriving in Germany. It provides evidence for an overall positive association between human and social capital and service utilization in general while also revealing differences in service domains. While language proficiency is positively associated with service utilization across all service domains, previous work experience in the country of origin particularly increases utilization of employment-related services. The analyses also find a positive association of inter-ethnic networks, whereas intra-ethnic connections are negatively associated with service utilization across many domains. The findings are especially relevant since they support the hypothesis of exclusive host community knowledge that benefits those refugees who engage with individuals outside their own ethnic network. The findings of this study accentuate the need to acknowledge the diversity of refugees' service needs as well as the barriers to service utilization that only well-equipped refugees seem to be able to overcome.
Keywords: 300; Refugees; Service utilization; Professional support services; Human capital; Social capital